Shifting Policies, Shifting Impacts: Evaluating Teacher Professional Allowance Distribution Reforms for Educators in Digital Era - Lailatul Fitriyah; Mufarrihul Hazin; Budi Purwoko; Kaniati Amalia; Amrozi Khamidi (IAIN Madura, 2025)
Teacher allowances are a key state obligation with significant implications for improving education quality. Transparent and efficient management is essential to ensure teachers receive their rightful support. This study explores a comparative analysis of two policies: (1) the Regulation of the Minister of Education and Culture No. 19/2019 and (2) the Regulation of the Minister of Primary and Secondary Education No. 4/2025, focusing on the policy transition and its impacts. Addressing previous research gaps, the study examines the shift from decentralized to centralized governance in State Junior High School in Mojokerto Regency. Using a qualitative approach, data were collected through observations, interviews, and document reviews. Findings show: (1) management shifted from local to central government, enhancing standardization and reducing bureaucratic dependence; (2) the 2025 model improved efficiency and consistency; and (3) while reforms show progress, the AGIL paradigm indicates further integration efforts are needed for sustainable quality improvement.